Peran Gen EPSPS dalam Ketahanan Tanaman Terhadap Herbisida: Prospek Dan Tantangan Kedepannya - Islamia, Mutmainnah Nur; Isrul, Muhammad; Hala, Yusminah (Symbiotic: Journal of Biological Education and Science, 2025)
Plant resistance to glyphosate herbicides has become a critical issue in modern agriculture. The 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS) gene is a key component of the shikimate pathway responsible for synthesizing essential aromatic amino acids in plants. Glyphosate inhibits the EPSPS enzyme, disrupting plant metabolism and leading to death. However, transgenic crops containing glyphosate-resistant EPSPS variants have been successfully developed, enabling effective weed control without harming cultivated plants. This study aims to review the role of the EPSPS gene in conferring glyphosate resistance, the underlying molecular mechanisms, and future prospects and challenges in its application. The method used is a literature review of scientific publications and credible sources concerning EPSPS function, plant transformation strategies, and their ecological impacts. The results indicate that the introduction of glyphosate-resistant EPSPS genes enhances weed management efficiency and agricultural productivity. Nonetheless, continuous and intensive use may accelerate the evolution of resistant weed populations, pose potential ecological risks, and raise issues of regulation and public acceptance. Therefore, sustainable management strategies, such as herbicide rotation and biotechnological innovations including CRISPR/Cas9-based editing, are necessary to ensure the long-term effectiveness and environmental safety of glyphosate-resistant crop technology.